The potential of blockchain technology in advancing sustainable energy: a study on the mediating role of specialization in the growth of Chinese hidden champions - Zhang, Chunyang; Zhu, Bingyan; Liu, Zeyan (Frontiers in Energy Research, 2023)
Innovation is a crucial factor for hidden champions to gain a competitive edge and foster organizational growth. This study focuses on Chinese-listed hidden champion firms between 2010 and 2019 and examines the impact of innovation heterogeneity on their growth. The study explores the impact of different types of innovation, including overall innovation, product innovation, and process innovation, and their interaction effects on the growth of hidden champions. The study also investigates the mediating role of the degree of specialization, which refers to the extent to which a firm focuses on a particular area of expertise. Furthermore, the potential of blockchain technology in advancing a sustainable energy future is becoming increasingly apparent. By enabling the creation of decentralized energy markets, blockchain can facilitate the integration of renewable energy sources, such as solar and wind power, into the grid. This can help to reduce carbon emissions and promote the transition to a low-carbon economy. The results of the study indicate that innovation, including overall innovation, product innovation, and process innovation, is significant for hidden champions’ growth. Moreover, the study reveals that product innovation and process innovation have complementary effects on the growth of hidden champions. The degree of specialization also plays a mediating role between different types of innovation and hidden champions’ growth. The results of this study provide empirical evidence to improve the growth of hidden champions from the perspective of enterprise innovation. By focusing on different types of innovation and understanding their complementary effects, firms can develop a more comprehensive innovation strategy that can enhance their growth potential. Moreover, the mediating role of degree of specialization highlights the importance of aligning innovation efforts with a firm’s core competencies to achieve sustained growth. This study contributes to the literature on hidden champions by shedding light on their innovation strategies and their impact on firm growth.